Does the timing of cytoreductive nephrectomy impact outcomes?: Analysis of REMARCC registry data for patients receiving tyrosine kinase inhibitor versus immune checkpoint inhibitor therapy - Meagher, Margaret; Minervini, Andrea; Mir, Maria C.; Cerrato, Clara; Rebez, Giacomo; Autorino, Riccardo; Hampton, Lance; Campi, Riccardo; Kriegmair, Maximilian; Linares, Estefania; Hevia, Vital; Musquera, Maria; et al. (European urology open science, 2024)
Background and objective - The role of cytoreductive nephrectomy (CN) in the treatment of metastatic renal cell carcinoma (mRCC) has been called into question on the basis of clinical trial data from the tyrosine kinase inhibitor (TKI) era. Comparative analyses of CN for patients treated with immuno-oncology (IO) versus TKI agents are sparse. Our objective was to compare CN timing and outcomes among patients who received TKI versus IO therapy. - Methods - This was a multicenter retrospective analysis of patients who underwent CN using data from the REMARCC (Registry of Metastatic RCC) database. The cohort was divided into TKI versus IO first-line therapy groups. The primary outcome was all-cause mortality (ACM). Secondary outcomes included cancer-specific mortality (CSM). Multivariable analysis was used to identify factors predictive for ACM and CSM. The Kaplan-Meier method was used to analyze 5-yr overall survival (OS) and cancer-specific survival (CSS) with stratification by primary systemic therapy and timing in relation to CN. - Key findings and limitations - We analyzed data for 189 patients (148 TKI + CN, 41 IO +CN; median follow-up 23.2 mo). Multivariable analysis revealed that a greater number of metastases (hazard ratio [HR] 1.06; p = 0.015), greater primary tumor size (HR 1.10; p = 0.043), TKI receipt (HR 2.36; p = 0.015), and initiation of systemic therapy after CN (HR 1.49; p = 0.039) were associated with worse ACM. A greater number of metastases at diagnosis (HR 1.07; p = 0.011), greater primary tumor size (HR 1.12; p = 0.018), TKI receipt (HR 5.43; p = 0.004), and initiation of systemic therapy after CN (HR 2.04; p < 0.001) were associated with worse CSM. Kaplan-Meier analyses revealed greater 5-yr rates for OS (51% vs 27%; p < 0.001) and CSS (83% vs 30%; p < 0.001) for IO +CN versus TKI + CN. This difference persisted in a subgroup analysis for patients with intermediate or poor risk, with 5-yr OS rates of 50% for IO + CN versus 30% for TKI + CN (p < 0.001). A subanalysis stratified by CN timing revealed better 5-yr rates for OS (50% vs 30%; p = 0.042) and CSS (90% vs 30%, p = 0.019) for delayed CN after IO therapy, but not after TKI therapy. - Conclusions and clinical implications - For patients who underwent CN, systemic therapy before CN was associated with better outcomes. In addition, IO therapy was associated with better survival outcomes in comparison to TKI therapy. Our findings question the applicability of clinical trial data from the TKI era to CN in the IO era for mRCC. - Patient summary - For patients with metastatic kidney cancer treated with surgery, better survival outcomes were observed for those who also received immunotherapy in comparison to therapy targeting specific proteins in the body (tyrosine kinase inhibitors, TKIs). Immunotherapy or TKI treatment resulted in better outcomes if it was received before rather than after surgery.
Online verfügbar: 25. März 2024, Artikelversion: 25. März 2024
Gesehen am 11.12.2024